Singular (p, q)-equations with superlinear reaction and concave boundary condition. Issue 3 (11th February 2022) - Papageorgiou, Nikolaos S.; Vetro, Calogero; Vetro, Francesca
Abstract : We consider a parametric nonlinear elliptic problem driven by the sum of a p -Laplacian and of a q -Laplacian (a ( p, q ) -equation) with a singular and ( p − 1 ) -superlinear reaction and a Robin boundary condition with ( q − 1 ) -sublinear boundary term ( q < p ) . So, the problem has the combined effects of singular, concave and convex terms. We look for positive solutions and prove a bifurcation-type theorem describing the changes in the set of positive solutions as the parameter varies.